Towards a less toxic etchig in Arts Education. - Chaves Badilla, Salomón Isaac (Arte, Individuo y Sociedad, 2010)
This review explores the immediate background concerning the artistic tendency of non-toxic or less toxic printmaker, started during the 1990’s in Europe and USA. Driven by concerns expressed by researchers (mostly artists and educators), due to the negative effects in human health exhibited by some traditional materials and procedures employed in creative printing. Additionally, technical and logistic advantages are comparatively analyzed for such methodologies, focusing on laminated photopolymer and its possible educative use in etching classes offered by the Faculty of Arts.
Keywords: Etching; Non-toxic printing; Arts Education; Contemporary printmaker